3D printing device - XU KALI; LIU JIANYE; GUAN ZIMIN; ZHU HAOWEI; LI SHUISHENG; GAO WENHUA; NIU LIUHUI; CAO XINGTONG; QI WENJUN; HUANG WENHUAN (2018)
The utility model provides a 3D printing device, includes: powder paving device for lay the powder at forming worktable, first laser instrument, including continuous laser seed source and pulsed laserseed source, fiber coupler and the optical fiber amplifier who sets gradually, continuous laser or pulsed laser are exported to the light beam of laser seed source and pulsed laser seed source outputbehind fiber coupler and optical fiber amplifier in succession, laser control module, with first laser instrument is connected, is used for control first laser instrument continuous laser of output or pulsed laser, the scanning galvanometer, be used for with laser or pulsed laser focus the forming worktable who lays the powder through the scanning galvanometer in succession, wherein: it is rightthat continuous laser is used for lay the forming worktable scanning shaping of powder, pulsed laser is used for carrying out the precision finishing to printing the formed part edge, the second laserinstrument is used for carr